Faktor Yang Mempengaruhi Profitabilitas Perbankan Syariah di Indonesia: Pasca Covid-19 - Sari, Mirna; Gibran, Khalil; Ramzijah, Ramzijah; Yanti, Evi Maulida (Universitas Muhammadiyah Ponorogo, 2024)
This study is a quantitative research that utilizes data collected from the financial statements of Islamic commercial banks in Indonesia from 2021 to 2023, focusing on the period after the COVID-19 pandemic. The research involves two independent variables: Non-Performing Financing (NPF) as variable X1 and Third-Party Funds (DPK) as variable X2, while the dependent variable is Return on Assets (ROA) (Y). The analytical method employed in this study is panel data regression, supported by software such as Microsoft Excel and Eviews. Data processing includes model selection tests, namely: a) The Chow test to determine whether to use the Common Effect Model (CEM) or the Fixed Effect Model (FEM). b) The Hausman test to decide between the Fixed Effect Model (FEM) and the Random Effect Model (REM). c) The Lagrange Multiplier test to choose between the Common Effect Model (CEM) and the Random Effect Model (REM). The results of the study reveal that both X1 and X2 variables, whether analyzed simultaneously or partially, do not have a significant impact on Return on Assets (ROA).